Key Aspects of German Employment and Labour Law - Kirchner, Jens.; Kremp, Pascal R.; Magotsch, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This publication gives an overview of all key aspects of German labour and employment law as well as adjoining fields. Legal professionals with expert knowledge and long years of experience explain the legal basis of these aspects of German law, point out typical practical problems and suggest solutions to those problems. Additionally, examples are given on how to best manage legal pitfalls to minimize risks. This book will especially help foreign in-house counsels and human resources managers at international companies to understand the complex legal regulations concerning labour and employment law in Germany. All three editors of the book, Dr. Jens Kirchner, Pascal R. Kremp and Michael Magotsch, are experienced legal professionals at the Frankfurt office of DLA Piper, one of the largest legal services providers in the world (www.dlapiper.com), with national and multinational clients. Their experience includes the management of cross-border restructurings, outsourcing and transfer of undertaking measures, as well as the management of national and multi-jurisdictional merger & acquisitions projects, including post-merger integration processes.
Executive Summary: German Employment and Labour Law -- Executive Summary: German Employment and Labour Law -- Employment Law -- Recruitment -- Employment Contracts and Further Legal Sources -- Employee or Freelance Worker -- Agency Workers -- Immigration -- Employee Secondments -- Pay and Benefits -- Working Hours, Holidays and Health and Safety -- Partial Retirement -- Diversity and Discrimination -- Data Protection and Monitoring -- Employee Inventions and Copyrights -- Non-Competition Clauses -- Termination of Employment -- Family Friendly Rights -- Managing Directors and Management Board Members -- Labour Law -- Unions and Collective Bargaining -- Labour Conflicts -- Employee Representation -- Restructuring -- Mergers and Acquisitions -- Business Transfers -- Stock Options -- Company Pensions -- Employee Co-Determination at Board Level -- Court Proceedings.
Keywords: Law; Social legislation; Law; Private International Law, International & Foreign Law, Comparative Law; Labour Law/Social Law; Human Resource Management